2022
DOI: 10.1093/nutrit/nuab078
|View full text |Cite
|
Sign up to set email alerts
|

Fish intake, n-3 fatty acid body status, and risk of cognitive decline: a systematic review and a dose–response meta-analysis of observational and experimental studies

Abstract: Context Randomized controlled trials (RCTs) testing supplementation with eicosapentaenoic (EPA) and docosahexaenoic (DHA) fatty acids have failed to provide evidence supporting a suggested inverse association between fish intake and dementia risk. Objective Dose–response analyses were conducted to evaluate associations between fish intake, all-cause dementia or Alzheimer’s Disease (AD), and the effect of EPA/DHA supplementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 67 publications
1
26
0
Order By: Relevance
“…A large number of epidemiological, clinical and experimental studies have been conducted over the past few decades investigating the role of long chain omega-3 polyunsaturated fatty acids (n3 PUFAs) for health. In particular, eicosapentaenoic acid (20:5, EPA) and docosahexaenoic acid (22:6, DHA) are viewed to have beneficial effects for cardiovascular disease (CVD) (1)(2)(3) , cancer (3,4) , diabetes (5,6) , metabolic syndrome (7) , dementia or Alzheimer's disease (8) , and depression (9) . However, results from randomized trials exploring the potential protective nature of n3 PUFAs on disease outcomes across this spectrum vary from beneficial to null (10) .…”
Section: Introductionmentioning
confidence: 99%
“…A large number of epidemiological, clinical and experimental studies have been conducted over the past few decades investigating the role of long chain omega-3 polyunsaturated fatty acids (n3 PUFAs) for health. In particular, eicosapentaenoic acid (20:5, EPA) and docosahexaenoic acid (22:6, DHA) are viewed to have beneficial effects for cardiovascular disease (CVD) (1)(2)(3) , cancer (3,4) , diabetes (5,6) , metabolic syndrome (7) , dementia or Alzheimer's disease (8) , and depression (9) . However, results from randomized trials exploring the potential protective nature of n3 PUFAs on disease outcomes across this spectrum vary from beneficial to null (10) .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to dairy and meat, association between fish intake and dementia outcomes or cognitive performance is more coherent. According to systematic reviews and metaanalyses, higher fish consumption associates with lower risk of dementia or AD [10][11][12][48][49][50]. The association between fish intake and cognitive performance is not as clear, as only one [13] of the two published systematic reviews [12,13] has found a beneficial association.…”
Section: Discussionmentioning
confidence: 99%
“…Diet is a rapid and direct way of modifying the gut microbiota composition and function, reducing inflammation, and helping in eubiosis maintenance [ 123 , 164 , 165 ]. Given the evidence of association between neuropsychiatric conditions and gut microbiota dysregulation, it is worth speculating that dietary interventions could represent effective candidates for preventing and delaying the pathogenesis and progression of AD [ 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 ] ( Table 2 ). Here, we present some of the most promising dietary therapies proposed in the literature, with a particular focus on Mediterranean and ketogenic diets.…”
Section: Mainmentioning
confidence: 99%
“…Differently, fish intake is inversely associated with AD—likely related to omega-3 (EPA/DHA) contents [ 195 ]. Interestingly, the regular consumption of fish up to two portions per week seems to be more protective than EPA/DHA supplementation [ 184 ]. Even though many studies are supporting the protective effect of unsaturated fatty acids EPA/DHA, their role in the brain is still under debate [ 200 , 201 , 202 , 203 , 204 ].…”
Section: Mainmentioning
confidence: 99%